Immunologic, genetic, and ecological interplay of factors involved in allergic diseases - Falcon, Robbi Miguel G.; Caoili, Salvador Eugenio C. (Frontiers in Allergy, 2023)
An allergic or type I hypersensitivity reaction involves a misdirected immune overreaction to innocuous environmental and dietary antigens called allergens. The genetic predisposition to allergic disease, referred to as atopy, can be expressed as a variety of manifestationse.g., allergic rhinitis, allergic conjunctivitis, atopic dermatitis, allergic asthma, anaphylaxis. Globally, allergic diseases are one the most common types of chronic conditions. Several factors have been identified to contribute to the pathogenesis and progression of the disease, leading to distinctively variable clinical symptoms. The factors which can attenuate or exacerbate allergic reactions can range from genetic heterozygosity, the prominence of various comorbid infections, and other factors such as pollution, climate, and interactions with other organisms and organism-derived products, and the surrounding environment. As a result, the effective prevention and control of allergies remains to be one of the most prominent public health problems. Therefore, to contextualize the current knowledge about allergic reactions, this review paper attempts to synthesize different aspects of an allergic response to describe its significance in the global health scheme. Specifically, the review shall characterize the biomolecular mechanisms of the pathophysiology of the disease based on underlying disease theories and current findings on ecologic interactions and describe prevention and control strategies being utilized. An integrated perspective that considers the underlying genetic, immunologic, and ecologic aspects of the disease would enable the development of more effective and targeted diagnostic tools and therapeutic strategies for the management and control of allergic diseases.